Analysis of high intensity activity in Premier League soccer - Di Salvo, V.; Gregson, W.; Atkinson, G.; Tordoff, P.; Drust, B. (International Journal of Sports Medicine, 2009)
The aim of the present investigation was to provide a detailed analysis of the high intensity running activity completed by elite soccer players during match-play. A further aim of the study was to evaluate the importance of high intensity running activity to overall team success. Observations on individual match performance measures were undertaken on 563 outfield players (median of 8 games per player; range=1-57) competing in the English Premier League from 2003/2004 to 2005/2006 using a computerised tracking system (Prozone®, Leeds, England). High intensity activities selected for analysis included total high intensity running distance (THIR), total sprint distance (TSD) and the number and type of sprints undertaken. Total high intensity running distance in possession and without possession of the ball was also analysed. The THIR was dependant upon playing position with wide midfield (1 049±106 m) and central defenders (681±128 m) completing the highest and lowest distance respectively (p<0.001). High intensity activity was also related to team success with teams finishing in the bottom five (919±128 m) and middle ten (917±143 m) league positions completing significantly more THIR compared with teams in the top five (885±113 m) (p=0.003). The THIR and TSD also significantly declined during the 2nd half with the greatest decrements observed in wide midfield and attacking players (p<0.05). Both positional differences in high intensity activity and the observed change in activity throughout the game were also influenced by team success (p<0.05). The results of the present study indicate that high intensity activity in elite soccer match-play is influenced by both playing position and previous activity in the game. These activity patterns are also dependant upon success of the team. This may indicate that overall technical and tactical effectiveness of the team rather than high levels of physical performance per se are more important in determining success in soccer.